The Gastroscopy RAte of Cleanliness Evaluation (GRACE) Scale: an international reliability and validation study - Esposito, Gianluca; Dilaghi, Emanuele; Costa-Santos, Cristina; Ligato, Irene; Annibale, Bruno; Dinis-Ribeiro, Mário; Areia, Miguel; GRACE Investigators; Arantes, Vitor N.; Bergman, Jacques; Bisschops, Raf; de Jonge, Pieter J. F.; Di Matteo, Francesco; Ebigbo, Alanna; Ferlitsch, Monika; Giljaca, Vanja; Hassan, Cesare; Hucl, Tomas; Kuvaev, Roman; Leclercq, Philippe; Matysiak-Budnik, Tamara; Mori, Yuichi; Moss, Alan; Pérez-Cuadrado-Robles, Enrique; Pouw, Roos E.; Rex, Douglas K.; Rodriguez de Santiago, Enrique; Siersema, Peter D.; Tham, Tony C.; Triantafyllou, Konstantinos; Voiosu, Andrei; Weusten, Bas; Andrisani, Gianluca; Angeletti, Stefano; Ayoub, Mousa; Bac, Simon; Boonstra, Kirsten; Borren, Nienke; Capogreco, Antonio; Chivato Martín Falquina, Irene; Chaves, Jéssica; Citterio, Nicolò; Dal Buono, Arianna; Dell’Unto, Elisabetta; Dragan, Victor; Elvas, Luís; Filimendikova, Ksenia; Frick, Adrian; Guardiola, John; Halvorsen, Natalie; Le Rhun, Marc; Libanio, Diogo; Macinga, Peter; Marini, Marco; Meijer, Berrie; Moresi Vianna de Oliveira, Rúbia; Nicolaides, Steven; Plomteux, Olivier; Prouvost, Victor; Samarentsis, Nikos; Sinonquel, Pieter; Tahir, Imran; Tang, Ken; Tenorio Gonzalez, Elena; Van de Ven, Steffi; Viegas, Maria Inês (Endoscopy, 2024)
Background Mucosal visualization during upper gastrointestinal (UGI) endoscopy can be impaired by the presence of foam, bubbles, and mucus. Some UGI endoscopy visibility scales have been proposed but have not undergone multicenter validation. This study aimed to develop and validate the Gastroscopy RAte of Cleanliness Evaluation (GRACE) scale.Methods A multicenter, international, cross-sectional study was conducted. The GRACE scale is based on a score from 0 (worst) to 3 (excellent) for esophagus, stomach, and duodenum, for a total ranging from 0 to 9. In phase 1, four expert endoscopists evaluated 60 images twice, with a 2-week interval between rounds; in phase 2, the same 60 images were scored twice by one expert and one nonexpert endoscopist from 27 endoscopy departments worldwide. For reproducibility assessment and real-time validation, the scale was applied to consecutive patients undergoing gastroscopy at each center.Results On internal validation, interobserver agreement was 0.81 (95 %CI 0.73–0.87) and 0.80 (95 %CI 0.72–0.86), with reliability of 0.73 (95 %CI 0.63–0.82) and 0.72 (95 %CI 0.63–0.81), in the two rounds, respectively. On external validation, overall interobserver agreement was 0.85 (95 %CI 0.82–0.88) and reliability was 0.79 (95 %CI 0.73–0.84). In real-time evaluation, the overall proportion of correct classifications was 0.80 (95 %CI 0.77–0.82).Conclusions The GRACE scale showed good interobserver agreement, reliability, and validity. The widespread use of this scale could enhance quality and standardize the assessment of mucosal cleanliness during UGI endoscopy, pushing endoscopists to strive for excellent visibility and reducing the risk of missed lesions.